Isotopic Radiolabeling of the Antiretroviral Drug [18F]Dolutegravir for Pharmacokinetic PET Imaging - Marion Tisseraud; Sébastien Goutal; Thomas Bonasera; Maud Goislard; Delphine Desjardins; Roger Le Grand; Chris M. Parry; Nicolas Tournier; Bertrand Kuhnast; Fabien Caillé (Pharmaceuticals, 2022)
Deciphering the drug/virus/host interactions at infected cell reservoirs is a key leading to HIV-1 remission for which positron emission tomography (PET) imaging using radiolabeled antiretroviral (ARV) drugs is a powerful asset. Dolutegravir (DTG) is one of the preferred therapeutic options to treat HIV and can be isotopically labeled with fluorine-18. [18F]DTG was synthesized via a three-step approach of radiofluorination/nitrile reduction/peptide coupling with optimization for each step. Radiofluorination was performed on 2-fluoro-4-nitrobenzonitrile in 90% conversion followed by nitrile reduction using sodium borohydride and aqueous nickel(II) chloride with 72% conversion. Final peptide coupling reaction followed by HPLC purification and formulation afforded ready-to-inject [18F]DTG in 5.1 ± 0.8% (n = 10) decay-corrected radiochemical yield within 95 min. The whole process was automatized using a TRACERlab® FX NPro module, and quality control performed by analytical HPLC showed that [18F]DTG was suitable for in vivo injection with >99% chemical and radiochemical purity and a molar activity of 83 ± 18 GBq/µmol (n = 10). Whole-body distribution of [18F]DTG was performed by PET imaging on a healthy macaque and highlighted the elimination routes of the tracer. This study demonstrated the feasibility of in vivo [18F]DTG PET imaging and paved the way to explore drug/virus/tissues interactions in animals and humans.